Coupled electron beam radiation and MBR treatment of textile wastewater containing polyvinyl alcohol. (July 2016) - Sun, Weihua; Chen, Jun; Chen, Lujun; Wang, Jianlong; Zhang, Yongming
Abstract: Advanced oxidation processes (AOP) can be combined with biological treatments for recalcitrant organic pollutant decomposition. However, there has been no thorough investigation on the coupling of AOPs and membrane bioreactors (MBR) to treat polymer organic pollutants. This study proposes a new AOP that couples electron beam (EB) radiation and MBR treatment. This method was applied to treat real textile effluents containing polyvinyl alcohol (PVA). During the stable operation stage, 31 ± 7% (n = 28) COD was removed by the EB-MBR process. COD removal was enhanced to 45% at the end of the research period without process optimization. In addition, both the membrane flux and activated sludge system exhibited good stability. Only a 2% membrane flux decreased was observed after a 46 d operation period. PVA radiolysis and biofacies analysis mechanisms are also discussed. By contrast, PVA degradation using only the MBR treatment was ineffective in this study. This ineffectiveness was caused by membrane interception and floccule formation by PVA and activated sludge. Highlights: We use electron beam coupled with an MBR to treat textile effluent containing PVA. Radiation products of the organic wastewater were well utilized by microbes in MBR. COD was steadily removed by the electron beam radiation-MBR treatment.